Experimental investigation of the thermal power pump cycle – Proof of concept. (April 2018) - Nihill, Jack; Date, Abhijit; Velardo, Jason; Jadkar, Sandesh
Highlights: Experimental investigation a novel power cycle to drive a thermal water pump. Examination of the theoretical performance of the experimental system. Experimental delivery heads of 20 m were achieved for a heat source of 80°C. Overall experimental efficiencies of 0.36%–0.48% were achieved. Abstract: This paper presents an experimental investigation of a water pump based on the thermal power pump (TPP) cycle. The pump is intended to effectively utilise low grade heat sources (below 100 °C) in order to pump water at high pressures. A piston-cylinder device has been created that operates on the TPP cycle and it is shown that significant delivery pressures are obtainable, up to 20 m head for a heat source of approximately 80 °C. The overall efficiencies obtained by the TPP system investigated here ranged from 0.36 to 0.48% for delivery heads from 5 to 20 m. The experimental results show that due to thermal cycling of the system, around 55–60% of heat input is not available for work conversion.